Preparation and Study of the Spectral and Structural Properties of Nano Composite Sensitize Photoelectrode - Mohammed, Haleemah J.; Taher, Ihab A.; Murad, Shatha F. (International Journal of Psychosocial Rehabilitation, 2020)
Nanocomposite (TiO2 -SnO2) has been prepared of raw materials chemically, addition, by Nd-YAG Laser (PLD for manufacturing sensitize photoelectrode for electrolysis cell to produce hydrogen, and studied spectral electrode using UV- VIS spectroscopy, Also, structured has been studied, through the analysis of (XRD). and (AFM) to identify the roughness of the prepared sample surface.